Clinical And Molecular Insights into Glanzmann’s Thrombasthenia in China - Zhou, Lu (Clin Genet, 2018)
Glanzmann’s thrombasthenia (GT) is a rare bleeding disorder characterized by spontaneous mucocutaneous bleeding. The disorder is caused by quantitative or qualitative defects in integrin αIIbβ3 (encoded by ITGA2B and ITGB3) on the platelet and is more common in consanguineous populations. However, the prevalence rate and clinical characteristics of GT in nonconsanguineous populations have been unclear. We analyzed 97 patients from 93 families with GT in the Han population in China. This analysis showed lower consanguinity (18.3%) in Han patients than other ethnic populations in GT-prone countries. Compared with other ethnic populations, there was no significant difference in the distribution of GT types. Han females suffered more severe bleeding and had a poorer prognosis. We identified a total of 43 different ITGA2B and ITGB3 variants, including 25 previously unidentified, in 45 patients. These variants included 14 missense, four nonsense, four frameshift, and three splicing site variants. Patients with the same genotype generally manifested the same GT type but presented with different bleeding severities. This suggests that GT clinical phenotype does not solely depend on genotype. Our study provides an initial, yet important, clinical and molecular characterization of GT heterogeneity in China.